Dear Reader! - Lukács, János (Public Finance Quarterly, 2024)
The editorial board of our journal is constantly striving to make the magazine better known and more accessible at home and abroad, and to further increase its position in the Scimago ranking. Following the suggestion of a sub-committee of the SCC for improvement, in this issue we are attempting to publish a partly different content for the Hungarian and English versions of our journal. Accordingly, one paper, one conference report and one review will be in Hungarian and English only, but the majority of articles will remain bilingual. We are looking forward to receiving readers’ reactions and opinions on this issue.